Nutrition literacy in sports: exploring sport type-specific effect on ergogenic aids utilization - Khairunnisa, Prima Amanda; Isaura, Emyr Reisha; Sari, Diandra Puspita (JURNAL KESMAS DAN GIZI (JKG), 2025)
Introduction: The role of nutrition in athletic performance is crucial. However, the nutritional requirements and literacy levels vary among athletes across different sports disciplines and influenced by various factors. Aims: This study investigates how nutrition literacy varies among athletes in different sports, exploring the factors, and examines the correlation between athletes' nutrition literacy levels and their use of ergogenic aids. Methods: This study employed a systematic literature review following the PRISMA method. Conducting searches across databases Scopus and PubMed using keywords including "nutrition literacy", "nutrition knowledge", "athletes", "sports", and "ergogenic." Results: Total of 18 selected articles show that nutrition literacy involves understanding food and nutrition to make informed dietary decisions, crucial for overall health. Enhanced literacy leads to healthier behaviors, particularly important for athletes. Variations in nutrition literacy among athletes across different sports disciplines are crucial for performance and well-being. Coaching emphasis, sport-specific demands, athlete demographics, and supplement use contribute to these variations, highlighting the importance of tailored education programs. Understanding athletes' knowledge and utilization of these aids, as well as their dietary practices, offers valuable insights into optimizing athletes’ performance. Factors such as the type of sport, individual preferences, and the availability of nutritional information play crucial roles in shaping athletes' decisions regarding ergogenic aid use. Conclusion: The connection between athletes' nutrition literacy and their use of ergogenic aids underscores the importance of tailored education and personalized nutrition plans for optimizing performance and well-being in sports.